Questioning the Anthropocene: Is It Really Our -Cene? - Simon C. Estok (New York City College of Technology, 2018)
Questioning the Anthropocene: Is It Really Our –Cene? by Simon C. Estok. This article shows that questioning the term Anthropocene does not mean denying devastating and irreversible anthropogenic effects on the world, and that even though other species certainly do refashion the world, what needs to be emphasized is that we are irreversibly altering the biosphere on a scale that threatens our own existence, that we are the only species currently doing these things with knowledge of their effects, and that we have the ability to change our ethics (and thus our behaviours) as a result of such knowledge.